2011
DOI: 10.1592/phco.31.4.338
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Microbiologic Outcomes in Trauma Patients Treated for Stenotrophomonas maltophilia Ventilator‐Associated Pneumonia

Abstract: Critically ill trauma patients with S. maltophilia VAP responded well to therapy despite high rates of inadequate empiric antibiotic administration. Trimethoprim-sulfamethoxazole was the most common therapy, but clinical success rates did not differ significantly based on antibiotic selection. This study adds significantly to the available S. maltophilia VAP outcomes data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
2
17
0
1
Order By: Relevance
“…In the study by Samonis et al, the authors attributed the low mortality to the inclusion of non-critically ill patients, and the inclusion of patients with all infection types. Other studies identified mortality rates of 21 to 33%, which are consistent with the in-hospital mortality rate seen in this cohort (7)(8)(9)(10)(11)(12)(13). Similar to other studies, the cohort was not limited to bloodstream infections and included infections at other sites.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In the study by Samonis et al, the authors attributed the low mortality to the inclusion of non-critically ill patients, and the inclusion of patients with all infection types. Other studies identified mortality rates of 21 to 33%, which are consistent with the in-hospital mortality rate seen in this cohort (7)(8)(9)(10)(11)(12)(13). Similar to other studies, the cohort was not limited to bloodstream infections and included infections at other sites.…”
Section: Discussionsupporting
confidence: 88%
“…Clinical data on the use of FQs for S. maltophilia are scarce, and most studies that evaluated clinical success included only patients treated with SXT or ␤-lactams (6)(7)(8)10). Other studies reporting outcomes for alternative options for S. maltophilia infections did not evaluate outcomes based on individual drug classes, and studies that did evaluate treatment …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations